Judicial activism contributing to the understanding of social state principle(s): Constitutional Court of Slovenia at the crossroads - Nejc Brezovar (DANUBE: Law, Economics and Social Issues Review, 2017)
The abstract nature of Constitutional principles, such as the social state principle, requires further interpretation to determine their concrete substance. Their realization is primarily the duty of politics and the legislator. Yet the Constitutional Courts can substantially contribute to developing the contents and nature of social state principles. This paper attempts to show, through examples from Slovenian judicature, how Constitutional Courts can, with the use of (limited) judicial activism, form and shape social politics and their main principles. The Slovenian Constitutional Court is usually relatively restrained in its interpretations of the social state principles respecting the primary authority of the legislator in regulating the area. On the other hand, we cannot ignore the important role the Constitutional Court and its judicature play in developing the substance of social state principles. This is usually done by means of dynamic and evolutionary interpretations. After analysing the judicature,we can conclude that some of the interconnected social state principals developed by the Court, which play a vital role in understanding the essence of a social state and social rights it provides, are: social balance, social security, social justice, solidarity, a minimum protection of existence, prevention of social exclusion, proving the important contribution of Constitutional Courts to the understanding of the concept of social state principals.
Keywords: 330; Social State; Constitutional Principle; Constitutional Court; Judicial Activism; Judicial Self-restraint; Welfare